The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1192/bjo.2018.64
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric profile and psychotropic medication use in adults with autism spectrum disorder: results from the Australian Longitudinal Study of Adults with Autism

Abstract: BackgroundChildren and adolescents with autism spectrum disorder (ASD) are a highly medicated group. Few studies have examined the neuropsychiatric profile and patterns of psychotropic medication use among adults with ASD.AimsTo describe and compare the neuropsychiatric profile and psychotropic medication use in a cohort of adults with ASD and non-autistic controls.MethodBaseline data from a survey-based, longitudinal study of adults with ASD in Australia. Participants were 188 adults with ASD and 115 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
2
12
2
Order By: Relevance
“…This may be one of the explanations for the recent findings that 71% of patients with intellectual disability were using psychotropic drugs without a recorded severe mental illness in order to manage their “mood dysregulation” (Sheehan et al, ). These findings were also replicated in a study looking at prescribing in people with autism (Cvejic, Arnold, Foley, & Trollor, ). This is also paralleled by our series where 79% were using antipsychotic medication despite only 3% having a psychotic disorder.…”
Section: Discussionmentioning
confidence: 58%
“…This may be one of the explanations for the recent findings that 71% of patients with intellectual disability were using psychotropic drugs without a recorded severe mental illness in order to manage their “mood dysregulation” (Sheehan et al, ). These findings were also replicated in a study looking at prescribing in people with autism (Cvejic, Arnold, Foley, & Trollor, ). This is also paralleled by our series where 79% were using antipsychotic medication despite only 3% having a psychotic disorder.…”
Section: Discussionmentioning
confidence: 58%
“…There were high numbers of recruitment responses across the four time 1 survey populations (autistic and control adult self-report, informant report on autistic adults, carer self-report). The ALSAA time 1 data have been used in several studies of psychotropic medication use,75 leisure participation,76 ageing well, 77 loneliness60 and employment 78. ALSAA and SASLA pooled data have been used to explore cognitive reappraisal,79 suicidal ideation,80 psychometric scale validation,64 and anxiety and depression 81.…”
Section: Findings To Datementioning
confidence: 99%
“…Following this protocol, future outputs such as peer-reviewed manuscripts, presentations and reports from the ALSAA will also be developed in consultation with autistic advisors or autistic peer researchers. Input from autistic advisors has already improved the quality and relevance of initial outputs,75 for example, identifying potential alternative interpretations of findings based on lived experiences, potential differences in autistic interpretations of scale items, and modifying the methodology in one instance60 changing a purely quantitative study into a mixed-methods design.…”
Section: Findings To Datementioning
confidence: 99%
“…Adolescents with ID are at significantly higher risk of ADHD than the general population (Reilly and Holland, 2011). There is little evidence regarding the prevalence of ADHD in people with ID but Cvejic et al (2018) reported a higher prevalence rate of ADHD in people with ID compared to studies in the general population. Studies in children with ID have shown a prevalence of ADHD of up to 40 per cent (Baker et al, 2010) but in contrast there is no evidence on the prevalence of ADHD in adults with ID.…”
Section: Adhd In Intellectual Disabilitiesmentioning
confidence: 94%